APPLICATION OF TOFU WASTE POC AND BIOCHAR COMPOST AND ITS EFFECTS ON SOIL AND PAKCOY - Djata Ndua, Natalia Desy; Bria, Deseriana; Naisali, Hyldegardis (Universitas Veteran Bangun Nusantara, 2025)
This study aimed to examine the effect of the application of Liquid Organic Fertilizer (LOF) of tofu waste and compost enriched with biochar on the content of C-organic, N-total, P-total, and P-available soil as well as the growth response and yield of pak choi. The study used a factorial completely randomized design (CRD). The first factor was the concentration of tofu waste LOF (4 levels), namely T0 (0 ml/L water), T1 (100 ml/L water), T2 (200 ml/L water), T3 (300 ml/L water). The second factor was the composition of biochar compost (4 levels), namely K0 (Soil), K1 (Soil: 10% biochar compost), K2 (Soil: 30% biochar compost), K3 (Soil: 50% biochar compost). The research parameters included C-organic, N-total, P-total, and P-available soil, plant height, and fresh weight of the shoot. The results showed that tofu waste LOF and biochar compost increased the content of C-organic, N-total, P-total and P-available soil. Furthermore, there was no interaction between tofu waste LOF and biochar compost on plant parameters. The single treatment of tofu waste LOF also had no significant effect on plant height and fresh weight of the crown, but biochar compost showed a significant effect on plant height and fresh weight of the crown with the best treatment being 50% biochar compost. This study proved that 50% biochar compost is able to improved soil chemical properties and increased pak choi growth and yield. Keywords: dry land, nutrients, planting media, soil chemistry, Timor